Hybrid biodegradable membranes of silane-treated chitosan/soy protein for biomedical applications. (July 2013) - Silva, Simone S; Oliveira, Joaquim M; Benesch, Johan; Caridade, Sofia G; Mano, João F; Reis, Rui R
In recent years, progress in the field of hybrid materials has been accelerated through use of the sol–gel process for creating materials and devices, which benefit from the incorporation of both inorganic and organic components. In this work, organic–inorganic hybrid membranes were prepared from tetraethoxysilane and a blend system composed of chitosan and soy protein. By introducing a small amount of siloxane bond into the chitosan/soy protein system, the chitosan/soy protein hybrid membranes were improved in terms of structure, topography and mechanical properties. It appears that the chitosan/soy protein hybrid membranes were formed by discrete inorganic moieties entrapped in the chitosan/soy protein blend, which improved the stability and mechanical performance assessed by the dynamic mechanical analysis as compared to chitosan/soy protein membrane. Also, in vitro cell culture studies evidenced that the chitosan/soy protein hybrid membranes are non-cytotoxic over a mouse fibroblast-like cell line. The hybrid membranes of silane-treated chitosan/soy protein developed in this work have potential in biomedical applications, including tissue engineering.